Comparison of vezikari and clark scale for determination of of viral intestinal infections sevitity and predicting their outputs in children - K. D. Ermolenko; N. V. Gonchar; M. K. Behtereva; Yu. V. Lobzin (Журнал инфектологии)
Introduction. To assess the severity of acute gastroenteritis in children, two scales of gravity are used: a 20-point Vesicari scale and a 24-point Clark scale. However, there are significant differences between these scales and there are practically no studies comparing their effectiveness in one representative group of patients. Material and methods: Complex clinical and laboratory examination of 143 children aged 1 to 7 with intestinal viral intestinal infections caused by rotavirus and norovirus was carried out. The severity of the patients’ condition was assessed using both Clark and Vesicary scale. Convalescences continued to be monitored for 12 months to open adverse outcomes. Results: In assessing the severity of viral intestinal infections using Clark and Vesicari scales, there were significant differences in children. The Vesicari scale significantly more accurately estimates the severity of intestinal infection in the acute period of the disease. At the same time, the use of the Clark scale contributes to the refinement of the prognosis for the development of post-infection gastroenterological pathology and its timely prevention. Conclusion: There is a need to create a new scale of universal assessment of the severity of viral intestinal infections that combines the advantages of both scales.